2023
DOI: 10.1038/s41467-023-37193-6
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length associates with chronological age and mortality across racially diverse pulmonary fibrosis cohorts

Abstract: Pulmonary fibrosis (PF) is characterized by profound scarring and poor survival. We investigated the association of leukocyte telomere length (LTL) with chronological age and mortality across racially diverse PF cohorts. LTL measurements among participants with PF stratified by race/ethnicity were assessed in relation to age and all-cause mortality, and compared to controls. Generalized linear models were used to evaluate the age-LTL relationship, Cox proportional hazards models were used for hazard ratio esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…Numerous studies have shown that shortened telomere length increased the risk of all-cause mortality [ 10 , 24 , 25 ]。In a study involving 472,432 participants from the UK Biobank, Schneider et al found that shortened LTL was positively correlated with all-cause mortality as well as disease-specific mortality for respiratory, digestive, circulatory, musculoskeletal, and infectious diseases [ 6 ]. Konstantin G Arbeev analyzed three European cohorts including a total of 3259 individuals and revealed that the risk of death from any cause increased by 1.34 times for every 1 kb decrease in LTL [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that shortened telomere length increased the risk of all-cause mortality [ 10 , 24 , 25 ]。In a study involving 472,432 participants from the UK Biobank, Schneider et al found that shortened LTL was positively correlated with all-cause mortality as well as disease-specific mortality for respiratory, digestive, circulatory, musculoskeletal, and infectious diseases [ 6 ]. Konstantin G Arbeev analyzed three European cohorts including a total of 3259 individuals and revealed that the risk of death from any cause increased by 1.34 times for every 1 kb decrease in LTL [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence shows that genetic factors play a role in some of ILD onset ( 74 , 75 ). It is now understood that certain inherited traits, such as rare pathogenic variants in genes associated with telomere maintenance and surfactant production ( 76 ), common single nucleotide polymorphisms ( 77 ), and reduced leukocyte telomere length can contribute to an increased risk of ILD ( 78 ).…”
Section: Etiologymentioning
confidence: 99%
“…This trend is particularly evident in IPF, where the disease predominantly affects individuals over the age of 65 ( 26 ). The association between aging and ILDs can be partially attributed to the biological process of telomere shortening ( 75 , 78 ). Telomeres, protective caps at the end of chromosomes, naturally shorten as individuals age, contributing to cellular senescence and reduced regenerative capacity ( 75 , 78 ).…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations